2002
DOI: 10.1080/00224540209603932
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of Employee Punctuality

Abstract: Although researchers have studied employee lateness empirically (e.g., S. Adler & J. Golan, 1981; C. W. Clegg, 1983), few have attempted to describe the punctual employee. In the present study, results of a discriminant analysis on employees in Israel indicated that a personality characteristic, time urgency, a subcomponent of Type A behavioral pattern, distinguished between punctual and late employees. Organizational commitment and age of employee's youngest child also distinguished between the groups.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(27 citation statements)
references
References 57 publications
0
26
0
1
Order By: Relevance
“…Take for instance lateness to work. In this case, lateness is typically defined as arrival at work after the time agreed upon by employer and employee (Dishon-Berkovits & Koslowsky, 2002). Time, however, can also be experienced subjectively (Hernadi, 1992).…”
Section: Meeting Lateness and Organizational Effectivenessmentioning
confidence: 99%
See 1 more Smart Citation
“…Take for instance lateness to work. In this case, lateness is typically defined as arrival at work after the time agreed upon by employer and employee (Dishon-Berkovits & Koslowsky, 2002). Time, however, can also be experienced subjectively (Hernadi, 1992).…”
Section: Meeting Lateness and Organizational Effectivenessmentioning
confidence: 99%
“…For meeting lateness to be considered a withdrawal behaviour, it must reflect, in part, underlying work-related attitudes (Dishon-Berkovits & Koslowsky, 2002). Importantly, however, this does not mean that environmental or individual factors do not matter; rather, to be considered a form of withdrawal, work attitudes just must factor in as well (Adler & Golan, 1981).…”
Section: Meeting Lateness Correlatesmentioning
confidence: 99%
“…Researchers have found, for example, that tardiness is predicted by low job satisfaction (Adler & Golan, 1981;Gupta & Jenkins, 1983) and by organizational commitment, employee's level of time urgency, and age of the employee's youngest child (Dishon-Berkovits & Koslowsky, 2002). To our knowledge, only one published study has investigated the relationship between employee tardiness and personality.…”
mentioning
confidence: 95%
“…This hypothesis is supported by Meyer et al (1993), who found that affective commitment was significantly negatively related to selfreported general tardiness. Several more studies have confirmed the relationship between commitment and lateness (Blau 1994;Blau et al 2004;Dishon-Berkovits and Koslowsky 2002;Foust et al 2006). As women's choices outside school are limited (Rosin and Korabik 1995), and as women in the teaching profession are able to cope more easily with the work-family conflict than other employed women, owing to their flexible hours and the short workday, it can be assumed that they are more committed to school than men and that the relationship between commitment and lateness will be stronger for them.…”
Section: Organizational Commitment Lateness and Gendermentioning
confidence: 90%